Photochemistry of organic compounds : - Klan, Petr. (Wiley, 2009)
Photochemistry of Organic Compounds: From Concepts to Practice provides a hands-on guide demonstrating the underlying principles of photochemistry and, by reference to a range of organic reaction types, its effective use in the synthesis of new organic compounds and in various applications.